Evaluation of bone health problems among a group of children with rheumatological diseases - Hala Lotfy; Somaia Mostafa; Hadeel Mohamed Seif; Hend Mohamed Abu Shady (Egyptian Pediatric Association Gazette)
Abstract Background Bone health problems such as decreased bone mineral density (BMD), osteopenia, and osteoporosis are major concerns during childhood as this period is the most critical for the development of optimum bone mass which is an essential determinant of bone health in adulthood. Secondary bone health problems are common among children with chronic diseases especially autoimmune diseases due to the inflammatory mediators, lack of appropriate physical activity, nutritional deficiencies, and side effects of medications. Aim of the work To evaluate BMD among a group of Egyptian children with juvenile idiopathic arthritis (JIA) and juvenile systemic lupus erythematosus (JSLE), and to study the association between bone health problems with different disease parameters, disease activity, and severity. Patients and methods Twenty-one children with JIA and 21 children with JSLE were assessed for bone health problems by thorough history taking, clinical examination, laboratory investigations including 25 (OH) vitamin D level, and evaluation of lumbar spine bone mineral density (LSBMD) by dual-energy X-ray absorptiometry (DEXA). LSBMD z-score results were adjusted according to height for age z-score (HAZ), we compared the results of LSBMD z-score to the HAZ-adjusted LSBMD z-score (LSBMDhaz) and correlated both with different JSLE and JIA disease parameters. Results Patients’ mean age was 9.9 ± 3.0 years, 12 (28.6%) were males and 30 (71.4%) were females. Most patients had decreased LSBMD. Low BMD frequency was higher among JSLE than JIA patients (p-value = 0.03). Mean ± SD of LSBMD z-score was − 1.73 ± 1.98 while the mean of LBMDhaz z-score was − 1.31 ± 1.70, there was no statistically significant difference between the two methods (p-value = 0.073). The LBMDhaz score detected more frequent abnormal LSBMD than non-adjusted LSBMD 29 (69%) and 19 (54.2%) respectively. Low LSBMD was not correlated with JSLE and JIA activity scores (p-value = 0.376 and 0.786 respectively), or the glucocorticoids (GC) dose in SLE and JIA (p-value = 0.203, 0.056 respectively) and duration (p-value = 0.203, 0.056 respectively). Most patients had decreased 25 OH vitamin D levels, 17 (40%) had insufficient and 7 (16.7%) had deficient levels. Conclusion Decreased LSBMD and vitamin D levels were detected among most of our JSLE and JIA patients. BMD should be monitored frequently among children with JIA and JSLE independent of disease severity or dose and duration of steroid therapy. Early detection and management of bone health problems improve the quality of life of these children.